Disaster-Causing Mechanism of the Continuous Failure of Deep Foundation Pits in Tropical Water-Rich Sandy Strata - Ping Lu; Zheng Shao; Jiangang Han; Ying Wang (Applied Sciences)
To investigate the mechanisms underlying the continuous failure of deep foundation pits in tropical water-rich sandy strata, this study comprehensively examines a foundation pit project in Haikou city, China. Using the PLAXIS3D 24.1 software, a three-dimensional finite element numerical model was developed. The analysis integrates design schemes, field investigations, monitoring data, and other relevant information to elucidate the mechanisms of disaster damage, such as foundation pit water inrush, floor collapse, and sidewall failure. The results indicate that the water barrier layer is the thinnest at the elevator shaft foundation pit, with a rapid shortening of seepage paths following the extraction of steel sheet piles; the seepage velocity increases by approximately 120%, leading to groundwater breaching both the water barrier and cushion layers. The inadequate length of the suspended impervious curtain in the confined aquifer results in a maximum seepage velocity at the defect site that is 40 times greater than that at other locations, facilitating groundwater influx into the foundation pit. As the excavation deepens, significant alterations occur in the groundwater seepage field at the defect location in the water-resisting curtain, with the seepage velocity increasing from 6.4 mm/day outside the pit to 78.8 mm/day inside the pit, thereby threatening the stability of the pit foundation. Additionally, construction quality defects arising from the three-axis mixing method in the silty sand layer cause a downward shift in the maximum horizontal displacement of the supporting structure, with displacement increments near the defects reaching 63%. Unreasonable emergency pumping measures can lead to floor collapses and sidewall damage. The soil in the pit significantly affects the back pressure, but it is also affected by the distance, and the increase in seepage velocity in the elevator shaft remains under 1% and does not significantly impact the damaging incident.